Penerapan Pidana Mati dalam Perspektif Undang - Undang No. 1 Tahun 2023 Tentang Kuhp Nasional - Adbaida Adbaida; Engrina Fauzi (CV. ITTC INDONESIA, 2026)
Law No. 1 of 2023 concerning the National Criminal Code, in Article 100 regulates the death penalty with a 10-year probationary period which has given rise to much debate and problems. In this article 100, there has been a shift in the paradigm of the death penalty from a principal punishment to a special punishment. This will open up a gap in legal uncertainty and the potential for transactional practices in assessing